n = 1 ∑ ∞ ( 2 n 4 n ) − 1 = X + Y π − Z Z 2 ln ( 2 1 + Z )
The equation above holds true for rational numbers X , Y , and Z . Find X Y Z .
Note : ( ⋅ ⋅ ) is the binomial coefficient . The first few terms of the series are as follows:
n = 1 ∑ ∞ ( 2 n 4 n ) − 1 = ( 2 4 ) 1 + ( 4 8 ) 1 + ( 6 1 2 ) 1 + ⋯ = 6 1 + 7 0 1 + 9 2 4 1 + ⋯ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hardest Brilliant problem I've seen. You can't even be bothered to give the solution. No, I didn't get it, but I did verify the approximate solution.
The cited page gives X=16/15
pi/sqrt(Y)=pi*sqrt(3)/27 from which Y=243
2/(Z sqrt(Z))=2 sqrt(5)/25 from which Z=5
XYZ=1296
sqrt(1296)=36
Log in to reply
X = 1 5 1 . Because In this question the lower summation limit starts from n = 1 .
There are two approaches that can lead to the exact solution. But for me, both of them requires programs like Wolfram Alpha or Mathetica to finish the last step.
Method 1
( n 2 n ) − 1 = ∫ 0 1 ( 2 n + 1 ) y n ( 1 − y ) n d y
With this identity, the answer will be:
∫ 0 1 ( 1 − z ) 2 1 + 3 z d y − 1 , z = ( y ( 1 − y ) ) 2
Method 2,
f ( x ) = n = 0 ∑ ∞ ( n 2 n ) − 1 x n
Then what we want is 2 f ( 1 ) + f ( − 1 ) − 1 .
f ( x ) = 2 F 1 ( 1 , 1 ; 2 1 ; 4 x )
Where 2 F 1 is the hypergeometric function.
Problem Loading...
Note Loading...
Set Loading...
The solution could be found here : see Theorem 3.8 on page 11. The last thing to be considered here is to ensure that the lower summation limits are not identical: 1 - here and 0 - via the link formulae.